Comprehensive evaluation and attribution analysis of baseflow variation in a typical karst basin, Southwest China - Chongxun Mo; Changhao Jiang; Shiting Long; Weiyan Cen (Journal of Hydrology: Regional Studies)
Study area: The study area was a typical karst basin in Southwest China, the Chengbi River Basin. Study focus: Studying baseflow variations and their influencing factors provides a scientific basis for sustainable water resource utilization and environmental protection. An adaptive baseflow research system for karst basins was established in this study, including the application of nine baseflow separation methods to reduce uncertainty in baseflow simulations, a more rational determination of annual and intra-annual baseflow characteristics, and an assessment of the impacts of climate change and human activities combining key meteorological elements and socio-economic indicators through the double-mass curve and SCRCQ methods. New hydrological insights for the region: This study’s findings showed that among the nine baseflow separation methods applied in the study area, the Boughton–Chapman digital filtering method was the most suitable. The annual baseflow showed a non-significant decreasing trend with no variability, and the intra-annual baseflow distribution was highly uneven. Climate changes were the main cause of baseflow variation in impact period T3 (1993–1998), while human activities were the main cause of baseflow variation in impact periods T2 and T4 (1979–1992, 1999–2019). This study proposes a relatively complete research system for baseflow in karst basins and provides an important reference for regional water resource development and management.